One Step at a Time: International Law and the Duty to Cooperate in the Management of Shared Water Resources - Leb, Christina (Taylor and Francis, 2014)
Analyzing the dynamics of international cooperation, this article describes the role of international law in the process. It illustrates that international law is a tool to achieve mutually beneficial relations and can be a driver for cooperation. Describing how these dynamics apply in the context of cooperation on transboundary rivers, the article traces the emergence of the general duty to cooperate in international water law as a legal response to the interdependence and coordination requirements in the management and development of shared water resources.